2021
DOI: 10.1002/clc.23586
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non‐recommended doses versus recommended doses of direct oral anticoagulants in atrial fibrillation patients: A meta‐analysis

Abstract: Background Several observational studies have shown that the inappropriate dosing use of direct oral anticoagulants (DOACs) in atrial fibrillation (AF) that does not conform to recommendations is becoming a widespread phenomenon. Therefore, we performed a meta‐analysis and systematic review to assess the effect of non‐recommended doses versus recommended doses of DOACs on the effectiveness and safety outcomes among AF patients. Methods The PubMed and Ovid databases were systematically searched to identify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
3
13
1
Order By: Relevance
“…In the present study, our results suggested that compared with the on-label dose of NOACs, the use of off-label underdose of NOACs was associated with increased risks of SSE and all-cause death but not IS, MI, and bleeding outcomes, whereas the use of off-label overdose of NOACs was associated with increased risks of SSE, all-cause death, and major bleeding but not MI and GI bleeding. Our current evidence further support the findings of previous meta-analyses ( 41 , 42 ) by adding the latest studies, suggesting the importance of appropriate NOAC dosing according to the NOAC-dose adjustment criteria.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, our results suggested that compared with the on-label dose of NOACs, the use of off-label underdose of NOACs was associated with increased risks of SSE and all-cause death but not IS, MI, and bleeding outcomes, whereas the use of off-label overdose of NOACs was associated with increased risks of SSE, all-cause death, and major bleeding but not MI and GI bleeding. Our current evidence further support the findings of previous meta-analyses ( 41 , 42 ) by adding the latest studies, suggesting the importance of appropriate NOAC dosing according to the NOAC-dose adjustment criteria.…”
Section: Discussionsupporting
confidence: 89%
“…The primary outcome was the initial stroke severity on admission, which was categorized based on the NIHSS score: mild (NI-HSS score ≤7), moderate (8)(9)(10)(11)(12)(13)(14)(15), and severe (≥16). The secondary outcome was a good functional outcome at 3 months, defined as an mRS score of 0-2.…”
Section: Outcomementioning
confidence: 99%
“…Indeed, the efficacy and safety of these inappropriate low-dose DOACs remain controversial. For example, prescribed underdoses of DOACs can increase the risk of stroke or systemic embolism, all-cause death [13], ischemic stroke [14], myocardial infarction [15,16], and bleeding complications [15,17]. Conversely, in some studies, patients prescribed underdoses of DOACs had similar risks for vascular events as those prescribed the recommended doses [13,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 As previously, several meta-analyses have explored the effects of off-label underdosing of NOACs on the effectiveness and safety outcomes in AF patients, suggesting that off-label underdosing of NOACs is associated with higher risks of thromboembolic complications and allcause death. [15][16][17] However, these studies combined different kinds of NOACs in their pooled analyses. Four NOACs are different from each other, including in their important pharmacological properties (e.g.…”
Section: Introductionmentioning
confidence: 99%